ANALISIS WACANA KRITIS DALAM PAGELARAN WAYANG KULIT LAKON “PETRUK DADI RATU” - Lanjar Rani; Pamerdi Giri Wiloso (Cakrawala Jurnal Penelitian Sosial, 2013)
This study took the title "Critical Discourse Analysis Pagelaran Wayang Kulit in Lakon "Petruk Dadi Ratu". This issued is a discourse that emerged from the shadow puppet Lakon Petruk Dadi Ratu. The purpose of this study was to determine the discourse of Lakon Petruk Dadi Ratu and why the discourse has a structure in such a way. Petruk Dadi Ratu is lakon carangan whose existence is played as a different opera and beyond pakemisasi pagelaran during the wayang kulit. The plot is lifted with a different feel and play with the new way of delivering mastermind who uses improvisation in the plot, according to his trademark. That's because the pattern of political and protest in the Lakon. One of them can be seen in the Lakon "Petruk  Dadi  Ratu".  The  play  is  an  improvised  play  where  puppeteers  give something more current and in accordance with the realities of life as a form of socio-political critique of what is going on in the current government.   Existence  pagelaran  puppet  puppeteer  with  skin  and  attitudes  provide moral  and  political  messages  interesting  to  study  through  critical  discourse analysis  approach.  This  study  uses  Critical  Discourse  Analysis  by  Norman Fairclough model approach. The data were analyzed in three dimensions, the dimension text, dimension discourse practices, and sociocultural dimensions. This study also uses Foucault's theory to see how the shadow puppets as a form of knowledge and power in a critical discourse analysis.  After analyzing the data obtained resulted in a change in the puppet world pakemisasi the other side in a leather puppet pagelaran. This was due to the progress of time to pack art and ideology became more interesting shadow play and can maintain its existence. This is shown through the play Petruk Dadi Ratu shadow puppets in a lakon carangan. Keywords:  Lakon  carangan,  Petruk  Dadi  Ratu,  power,  leadership,  critical discourse analysis.